(untitled) (Research, Society and Development, 2021)
The objective was to address, in the perception of the cooperative members who participated in the research, the main aspects involved in the organization of production, management and marketing of bee products, focusing on the importance of the Beekeepers Cooperative. The survey was conducted with 66% of the total cooperative beekeepers. A survey of primary data with beekeepers was carried out. For this, the survey method was used through a Structured and Undisguised form. It was observed that less than half of beekeepers carry out the beekeeping activity on their own land. The product that stood out in the beekeeping production of Vale do Jequitinhonha was honey. 33% of beekeepers use an area of 1 to 20 ha for beekeeping and only 14% of respondents mention that beekeeping is the only source of income. Among the interviewed beekeepers, 67% have been cooperated for at least 10 years. Regarding the commercialization of bee products, it was observed that 43% of beekeepers market their products totally or partially without the intermediary of the cooperative. Many of the beekeepers interviewed reported a lack of adequate infrastructure for collecting and managing honey. In this sense, the presence of a cooperative can be considered an advantage, as it offers associated beekeepers an adequate infrastructure for collecting honey. In the opinion of 71% of the interviewed beekeepers, the cooperative’s performance is classified as good or very good. It is concluded that strategies focused on collective actions need to be prioritized to consolidate the links between those involved and provide the necessary condition for the strengthening of regional beekeeping.